Efeito da adubação orgânica na produção de fitomassa e nos compostos bioativos de Passiflora incarnata L - Campos, Márcio Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to evaluate the growth of biomass of Passiflora incarnata L. in response to different levels of organic fertilizer on the content of total polyphenols, total flavonoids and antioxidant capacity in leaves and stems of wild passion. The experiment was conducted with family farmers. Seedlings were grown in a greenhouse and then transplanted to the field with spacing 0.30 m x 0.60 m, the thicket system irrigated by sprinkler. The experimental design was a randomized block design with seven treatments and four blocks (T1: control, T2: lime; T3: limestone + organic matter; T4: limestone + manure + organic matter; T5: limestone + manure + organic matter + Yoorin; T6: 1 organic commercial production; T7: organic commercial production 2. The organic fertilization and liming were made in the row with rabbit manure, chicken manure, organic waste and dolomitic limestone 30 days before transplanting. The extract for analysis of the levels of total flavonoids was performed according to the spectrophotometric method. The total polyphenols were evaluated according to the spectrophotometric method using the Folin-Ciocalteau reactive in the leaves and stems, which were dried in an oven with air circulation at 40° C / 48 h. Concluded from the results, the organic fertilizer provides a positive and significant effect on the development of plants with increased biomass dry matter production response. The results of total flavonoid content in the leaves show levels of these substances with differences in treatment. Treatment 6 had the highest rate among treatments. Treatment 3 had the lowest average statistics between the results of flavonoids. For the production of bioactive compounds such as polyphenols, flavonoids and antioxidant capacity in P. incarnata for acreage there was no significant interaction with the organic fertilization

O objetivo deste trabalho foi avaliar a produção de fitomassa de Passiflora incarnata L. em função de diferentes níveis de adubação orgânica e os teores dos polifenóis totais, flavonoides totais e capacidade antioxidante (TEAC - Capacidade Antioxidante em Equivalente Trolox) em folhas e caule do maracujá-silvestre. O experimento foi realizado com produtores rurais familiares de Botucatu, entre outubro de 2013 e fevereiro de 2014. Mudas foram produzidas em casa de vegetação e posteriormente transplantadas para o campo com espaçamento 0,30 m x 0,60 m, sem tutoramento, pelo sistema de moita, irrigadas por aspersão. O delineamento experimental foi em blocos ao acaso, com sete tratamentos e quatro blocos (T1: testemunha; T2: calcário; T3: calcário + matéria orgânica; T4: calcário + matéria orgânica + esterco; T5: calcário + matéria orgânica + esterco + yoorin; T6: produção comercial orgânica 1; T7: produção comercial orgânica 2. A adubação orgânica e a calagem foram feitas em tratamentos de plantio com esterco de coelho, esterco de frango, resíduo orgânico e calcário dolomítico 30 dias antes do transplantio. A extração e análise dos teores dos flavonoides totais foram realizadas de acordo com o método indicado em literatura. Os polifenóis totais foram avaliados de acordo com o método espectrofotométrico com o uso do reativo de Folin-Ciocalteau, nas folhas e caule do maracujá-silvestre, que foram secos em estufa com circulação de ar a 40 °C/48 h. Na diferenciação dos tratamentos com adubos orgânicos conclui-se a partir dos resultados obtidos, que a adubação orgânica confere uma resposta positiva e com efeito significativo sobre o desenvolvimento vegetativo da planta com o aumento da produção de fitomassa de matéria seca. Os resultados de teores de flavonoides totais nas folhas mostram níveis destas substâncias com diferenças estatísticas ...
Effect of organic fertilizer on biomass production and the bioactive of the Passiflora incarnata L
Keywords: Maracuja; Química vegetal; Plantas medicinais; Flavonoides; Medicinal plants